A Voltage Balancing Control Strategy for Modular Multilevel Converter Based on Allowable Capacitance Voltage of Sub-modules - Binqiao ZHANG; Cheng LI; Zhenxing LI; Bowen XIAO; Chuang LIU; Fei WANG (Zhongguo dianli)
Aiming at the problems of high switching frequency, large switching loss and large amount of computation in traditional voltage balancing strategy for modular multilevel converter (MMC), an improved capacitor voltage balancing control strategy is proposed. The sub-module (SM) voltage is constantly kept in the specified range through introducing the allowable value variable of capacitor voltage, consequently reducing the loss of power devices. In the meantime, all the sub-modules need not to be sorted in each control cycle, thus further reducing the amount of computation of the control strategy. Finally, the Matlab/Simulink-based simulation is carried out and the results show that the proposed strategy can significantly reduce the switching times of power devices per unit time.